1975
DOI: 10.1677/joe.0.0650219
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the Ovary to Gonadotrophins in Pre- And Perinatal Life: Oestrogen Secretion in Tissue and Organ Cultures

Abstract: Secretion of oestrogen by the ovaries of foetal (15-19 days of gestation) and newborn rats in organ and tissue culture was not detectable by fluorometry when the ovary was taken from foetuses before folliculogenesis had occurred. In organ cultures of ovaries, the time of folliculogenesis corresponded with the normal timing of folliculogenesis in vivo. In tissue cultures the process of formation of follicles was delayed. Oestrogens were present in the medium when folliculogensis was fully established in the cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…More recent serum and tissue analyses from newborn rats and mice have revealed increases in ovarian estrogen in response to hCG (human chorionic gonadotropin), LH, FSH, and cAMP (cyclic adenosine 3Ј,5Ј-monophosphate) around 1 week after parturition (Mannan & O'Shaughnessy 1991;Sokka & Huhtaniemi 1995;Weniger et al 1993). Ovarian hypertrophy in response to unilateral gonadectomy has been observed as early as Day 10 in the rat (Gerall & Dunlap 1971), and estrogen synthesis has been observed in neonatal ovarian tissue cultured in vitro (Funkenstein et al 1980;Levina et al 1975). These findings support the view that ovarian estrogen could exert developmental effects in the neonatal period following the decline of AFP.…”
Section: Onset Of Ovarian Activitymentioning
confidence: 99%
“…More recent serum and tissue analyses from newborn rats and mice have revealed increases in ovarian estrogen in response to hCG (human chorionic gonadotropin), LH, FSH, and cAMP (cyclic adenosine 3Ј,5Ј-monophosphate) around 1 week after parturition (Mannan & O'Shaughnessy 1991;Sokka & Huhtaniemi 1995;Weniger et al 1993). Ovarian hypertrophy in response to unilateral gonadectomy has been observed as early as Day 10 in the rat (Gerall & Dunlap 1971), and estrogen synthesis has been observed in neonatal ovarian tissue cultured in vitro (Funkenstein et al 1980;Levina et al 1975). These findings support the view that ovarian estrogen could exert developmental effects in the neonatal period following the decline of AFP.…”
Section: Onset Of Ovarian Activitymentioning
confidence: 99%
“…Although it has been shown in tissue culture that rat ovaries do not produce oestrogen after HCG stimulation (Levina et al, 1975), fetal ovaries do possess the enzymes required for steroidogenesis, and can respond to stimulation by prostaglandin PGE, with increased CAMP formation (Lamprecht et al, 1973). On the whole the role of pituitary secretion in ovarian endocrine function in utero seems limited.…”
Section: Gonadal F U N C T I O N I N T H E Fetusmentioning
confidence: 99%
“…The state of vaginal smears and ovarian histology appear to indicate that hOG-primed mice undergo a slight degree of persistent-estrus syndrome. Levina et al (1975) have reported that secretion of estrogen by the ovaries of fetal rats was not detectable from days 15 to 19 of gestation. Presl et al (1969) have demonstrated the presence of estrogen in the blood of normal rats only when the animals attained the age of 8 days.…”
Section: Discussionmentioning
confidence: 99%